A Modern Ampelography: A Genetic Basis for Leaf Shape and Venation Patterning in Grape. Issue 1 (27th November 2013) - Chitwood, Daniel H.; Ranjan, Aashish; Martinez, Ciera C.; Headland, Lauren R.; Thiem, Thinh; Kumar, Ravi; Covington, Michael F.; Hatcher, Tommy; Naylor, Daniel T.; Zimmerman, Sharon; Downs, Nora; Raymundo, Nataly; et al.
Abstract : Statistical methods can globally describe the complex shapes of grape leaves, permitting the evaluation of not only the genetic basis of leaf shape but its correlation with traits of economic interest . Abstract: Terroir, the unique interaction between genotype, environment, and culture, is highly refined in domesticated grape ( Vitis vinifera ). Toward cultivating terroir, the science of ampelography tried to distinguish thousands of grape cultivars without the aid of genetics. This led to sophisticated phenotypic analyses of natural variation in grape leaves, which within a palmate-lobed framework exhibit diverse patterns of blade outgrowth, hirsuteness, and venation patterning. Here, we provide a morphometric analysis of more than 1, 200 grape accessions. Elliptical Fourier descriptors provide a global analysis of leaf outlines and lobe positioning, while a Procrustes analysis quantitatively describes venation patterning. Correlation with previous ampelography suggests an important genetic component, which we confirm with estimates of heritability. We further use RNA-Seq of mutant varieties and perform a genome-wide association study to explore the genetic basis of leaf shape. Meta-analysis reveals a relationship between leaf morphology and hirsuteness, traits known to correlate with climate in the fossil record and extant species. Together, our data demonstrate a genetic basis for the intricate diversity present in grape leaves. We discuss the possibility of using grape leaves as a breeding target to preserve terroir in the face of anticipated climate change, a major problem facing viticulture.